PENGARUH PENEMPATAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada PG Tjoekir Jombang) - Cici Rosita Devi; Eko Agus Susilo; Anandhayu Mahatma Ratri (University of Merdeka Malang, 2016)
This research conducted in Jombang Tjoekir PG aims to determine how the effect of staffing and job satisfaction on employee performance. The total sample of 133 respondents and the sampling technique using random sampling. This research used path analysis. The results of the regression analysis showed that the direct effect with probability value of 0,329 and path coefficient of 0,000. So it can be concluded that supported the hypothesis 1. The result of the regression analysis showed that the direct effect on staffing toward to job satisfaction has significant effect with probability value of 0,000 and path coefficient value of 0,464, so it can be concluded that the result supported the hypothesis 2. The result of the regression analysis showed that the direct effect on staffing toward to employee performance has significant effect with probability value of 0,400 and path coefficient value of 0,000 so it can be concluded that the research result support the hypothesis 3 because there is a significant relationship between job satisfaction on employee performance. The total effect is larger (0.460) compared to its direct effect on the staffing of variable toward to performance of employees (0.329) and the indirect effect of (0.131). This means that the staffing variable of amplifying the job satisfaction and employee performance variable, so the hypothesis 4 is accepted. This can be shown by the Adjusted R-square value was 0.357 or 35.7% with a significance of 0.000. This means that only 35.7% performance of employees variable affected by the variable staffing and job satisfaction while the remaining 64.3% is influenced by other variables.